Towards a Simulation-based Communication Tool to Support Semantic Business Process Management - O'SULLIVAN, DECLAN; CONLAN, OWEN (My University, 2008)
Successfully communicating a Business Executive?s goals and desires to an IT Architect with regard to organizational change presents a major challenge. The most significant problem is relating the changes desired in a semantically consistent and understandable manner and then reflecting the potential impact of those changes on the organizational structure and the business processes carried out within that organization. This paper presents a proposal for a simulation-based communication tool that employs a semantically driven natural-language component to capture a Business Executive?s needs. These needs are translated into a simulation of a business process consisting of semantic web services that represent the evolution of the organizations IT infrastructure and policies. Through an iterative communication loop with the IT Architect the simulation can be used to accurately represent the changes necessary to meet the Business Executive?s needs.
Third International Workshop on Semantic Business Process Management in Proceedings of Workshops held at the Fifth European Semantic Web Conference (ESWC08)
PUBLISHED
Keywords: Natural Language; SBPM